2017
DOI: 10.1371/journal.pone.0176075
|View full text |Cite
|
Sign up to set email alerts
|

Non invasive imaging assessment of the biodistribution of GSK2849330, an ADCC and CDC optimized anti HER3 mAb, and its role in tumor macrophage recruitment in human tumor-bearing mice

Abstract: The purpose of this work was to use various molecular imaging techniques to non-invasively assess GSK2849330 (anti HER3 ADCC and CDC enhanced ‘AccretaMab’ monoclonal antibody) pharmacokinetics and pharmacodynamics in human xenograft tumor-bearing mice. Immuno-PET biodistribution imaging of radiolabeled 89Zr-GSK2849330 was assessed in mice with HER3 negative (MIA-PaCa-2) and positive (CHL-1) human xenograft tumors. Dose dependency of GSK2849330 disposition was assessed using varying doses of unlabeled GSK284933… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 29 publications
5
34
1
1
Order By: Relevance
“…PET imaging with a 89 Zr-labeled mAb may be used to gain better insight into the in vivo behavior of antibodies. 1,12,13 For any immunotherapeutic antibody evaluation, the first and foremost issue is to assess target saturation, which is helpful for effective therapy dose selection. In this study, dose escalation PET imaging was performed, and the dosedependent target engagement was first evaluated for a BsAb.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PET imaging with a 89 Zr-labeled mAb may be used to gain better insight into the in vivo behavior of antibodies. 1,12,13 For any immunotherapeutic antibody evaluation, the first and foremost issue is to assess target saturation, which is helpful for effective therapy dose selection. In this study, dose escalation PET imaging was performed, and the dosedependent target engagement was first evaluated for a BsAb.…”
Section: Discussionmentioning
confidence: 99%
“…8,11 Studies have shown that molecular imaging can be used to assess target engagement. [12][13][14] In 2017, Alsaid et al investigated GSK2849330 HER3 receptor occupancy in HER3-positive xenograft tumors (BxPC3, and CHL-1) by near-infrared fluorescence optical imaging. 12 Another report by Burvenich et al showed that gamma camera imaging of the 111 In-labeled anti-DR 5 antibody CS-1008 can be used to measure DR5 target saturation in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor and normal-tissue uptake were evaluated, and the effect of therapeutic doses of GSK2849330 mAbs (GlaxoSmithKline) on tumor uptake was assessed as an indicator of receptor occupancy. This report follows an earlier preclinical PET study in which 89 Zr-GSK2849330 mAbs (0.5 mg/kg; 5 MBq) were administered to mice with HER3-positive CHL-1 human melanoma xenografts or HER3-negative MIA-PaCa-2 human pancreatic tumors (9). In this earlier study, PET showed lower uptake of 89 Zr-GSK2849330 in MIA-PaCa-2 than in CHL-1 tumors, and tumor uptake of 89 Zr-GSK2849330 was blocked by preadministering a 100-fold excess of unlabeled GSK2849330 (50 mg/kg), revealing that tumor uptake was HER3-specific.…”
mentioning
confidence: 94%
“…HER3 overexpression has been implicated in resistance to cancer treatment. There have been only a few reports of immuno-PET to assess expression of HER3 on tumors preclinically (9,16) or clinically (14,17). The immuno-PET studies reported by Menke-van der Houven van Oordt et al (8) and by others (14,17) demonstrate the feasibility of imaging HER3 in patients with cancer.…”
mentioning
confidence: 99%